2021
DOI: 10.1111/ecc.13423
|View full text |Cite
|
Sign up to set email alerts
|

Cancer care near the end‐of‐life in Austria: A retrospective data analysis

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
(22 reference statements)
2
5
1
Order By: Relevance
“…Our study supports the evidence from previous investigations that PC admission has a relevant role in reducing various indicators of EOL aggressive care 5–14. In particular, we found that PC reduced hospitalisations by over 70%, long hospital stay by 75%, ED visit by 65%, and use of chemotherapy by 35% during the last month.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our study supports the evidence from previous investigations that PC admission has a relevant role in reducing various indicators of EOL aggressive care 5–14. In particular, we found that PC reduced hospitalisations by over 70%, long hospital stay by 75%, ED visit by 65%, and use of chemotherapy by 35% during the last month.…”
Section: Discussionsupporting
confidence: 91%
“…With reference to the indicators of aggressive EOL care analysed in our study, we found that about 45% of patients were hospitalised during the last 30 days of life, a value that is within the range between 40% and 65% reported in previous investigations 10–14 28. About 30% of patients with cancer in Lombardy died in hospital, a value among the lowest reported in other studies (between 30% and 70%) 4 10 11 13–15 17 28.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…6 The treatment aggressiveness is not high or increasing universally. There are examples of low levels of aggressiveness in Austria 11 and even decreasing aggressiveness, although still at a high level. 7 It may be argued that the introduction of immunotherapy and targeted therapy allowed treating patients less aggressively and prolonged survival.…”
Section: Discussionmentioning
confidence: 99%